Spindle Cell Pseudotumor Mimicking Malignancy in an Immunocompetent Patient with a Left Ventricular Assist Device. Issue 1 (2018) - Farkas, Zahava C.; Chawla, Lavneet; Frager, Shalom; Esses, Edward; Yusuf, Yasmin; Dworkin, Brad
ABSTRACT : N/A: Cytomegalovirus (CMV)‐induced pseudotumors, or mass‐like lesions in the colon, are a rare entity. We report a case of CMV‐related spindle cell pseudotumor in an immunocompetent patient with a left ventricular assist device. This case highlights the importance of considering CMV‐induced inflammatory pseudotumor when evaluating tumorous lesions in the colon, as well as the importance of appropriate diagnostic work‐up, including proper biopsy technique and meticulous review of the pathology.